Ekspresi Beragama Komunitas Tionghoa Aceh dalam Melaksanakan Ta Fo Ci di Takengon, Aceh Tengah - Rosnida Sari (Indonesia Social Justice Network (ISJN), 2021)
This paper looks at the ritual which carrying out of Ta Fo Ci for Buddhist believer in Vihara Takengon, Central Aceh. This reseach was conducted with descriptive qualitative method. This research was used in- depth interview technique with Ta Fo Ci participants. This research found that the implementation of Ta Fo Ci was not only folloewd by Buddist people in Aceh but also from Medan, Jakarta and even from abroad such as Malaysia, Singapore and Australia. This activity is the result of self-sufficiency from Buddhist who come to worship at the place. Initially this actvity was only held for 7 days, but since 2019 this activity was carried out for 14 days because of increasing attention of the participants. Unfortunately, the activity that has been carried out for 37 years has not received any attention from the government, only later in 2020 the Buddhist leader give awards to the Ta Fo Ci participants. Beside, this activity was never publish in local or national media so that this activity seemed closed. The information provided for this activity was also only due to the proximity between the Ta Fo Ci participants. This study recommends that this activity can be carried out in close proximity to the other regional activities such as the Gayo Cultural Parade so that while worshiping participants from various countries can witness and learn about Gayo traditions and customs.